Pengembangan Media Lembar Kerja Siswa (LKS) Berbasis Web Pada Mata Pelajaran Jaringan Dasar - Juaeni Abadi; Baiq Desi Dwi Arianti; Rasyid Hardi Wirasasmita (Jurnal Pendidikan Informatika (EDUMATIC), 2018)
The aims of  this study is to develop teaching materials in the form of Web-Based Student Worksheet on the subjects of Basic Network at SMK Negeri 1 Sikur through web design development process and performance testing and system feasibility. The development model used in this research is the System Development Life Cycle (SDLC) Model with Waterfall method consisting of 4 main stages of development. The first stage is the analysis requirement that is divided into 2 namely the functional analysis and development analysis. The second stage is Design, consisting of system design using UML, interface design as well as database design. The third stage is the implementation and the fourth stage is testing, Based on the results of software testing that has been developed shows the results as follows: (1) manufacture of teaching materials in the form of Web-Based Student Worksheet has been through the process of web development from analysis to testing in accordance with web check list and system functions, (2) the performance of teaching materials in the form of Web-Based Student Worksheet as a whole fall into the category of "Eligible" with a percentage rate of 78.94%.